Toxidade aguda e crônica em girinos de Physalaemus gracilis (Anura : Leptodactylidae) expostos à atrazina e tebuconazole - Sturza, Paola Flores (2017)
Pesticides, represented by chemical substances, also known as agrochemicals, have the objective of controlling agricultural pests. However, they may be harmful to the biological systems of various aquatic organisms, including anuran amphibians. It is important to evaluate effects through toxicological tests that provide information on the response to contaminants in an organism. This study evaluated the toxicological effects caused to species of anuran amphibian Physalaemus gracilis exposed to the herbicide atrazine and the fungicide tebuconazole. For this, the total direct nature spawnings with less than 24 hours of oviposition were collected and transported to the laboratory where they were kept under controlled conditions for their development. After that was performed the acute toxicity test for 96 hours to determine the LC50 and, subsequently, the chronic test, where mortality, morphological alterations and biochemical alterations of tadpoles exposed to sublethal concentrations were evaluated. To calculate the LC50 was employed the trimed spearman karber method. The LC50 for atrazine was 47.90 mg/L, meanwhile for tebuconazole was 1.64 mg/L. The exposure to sublethal doses caused changes in the oral morphology of tadpoles, such as absence of jaw, absence of one or more whole rows of denticles, rows of crooked teeth, missing or missing teeth, and edema of the intestine. In addition, atrazine and tebuconazole caused oxidative damage inducing effects on Physalaemus gracilis tadpoles. The occurrence of lipid peroxidation and carbonyl proteins suggest oxidative damage of the lipids and proteins.